Digitalization, Service Quality, and Maternal-Child Health Program Performance in East Java - Titin Irawati; Eddy Yunus; Slamet Riyadi; Bambang Raditya Purnomo; Sukesi Sukesi (Penerbit Goodwood, 2026)
Purpose: This study examined the effects of organizational culture, competence, motivation, and infrastructure on service quality and maternal-child health program performance in East Java. It also investigates the mediating role of service quality and the moderating role of digitalization in the relationship between service quality and program performance.Methodology: A quantitative cross-sectional survey was conducted involving 400 coordinating and maternal-child health midwives from community health centers across ten high-priority districts in East-Java. Data were collected using a structured Likert-scale questionnaire and analyzed using IBM SPSS Statistics 30.0, JASP 0.95.0.0, and SmartPLS 4.0.Results: Competence, motivation, and infrastructure significantly enhanced service quality, whereas organizational culture had no significant effect. Organizational culture and infrastructure significantly improved maternal-child health program performance, whereas competence, motivation, and service quality did not exhibit significant direct effects. Digitalization significantly strengthened the relationship between service quality and program performance at moderate- and high-level digitalization.Conclusions: Service quality contributes to the performance of maternal-child health programs when supported by integrated digital monitoring and alert-response systems.Limitations: The cross-sectional design and reliance on self-reported data limit the causal inference.Contributions: This study proposes a digitalized performance dimension for maternal-child health governance, encompassing data completeness, synchronization timeliness, digital early detection accuracy, dashboard utilization, alert response, and user digital satisfaction.